Performance Evaluation for Related Techniques of the Proposed Environment Pollution Monitoring System for an Iraqi Case Study - Taha E. Al-jarakh; Osama Abbas Hussein; Alaa Khamees Al-azzawi; Mahmood Farhan Mosleh (Journal of Techniques)
The main challenge of this research is to scale the IoT platform aspects related to exchanging, processing, and archiving messages at the lowest cost compute-wise, through evaluating and selecting the most appropriate techniques that can be used in the design of the environment pollution monitoring system for a case study of Iraq. The entirety of the optimization process aims to provide a nation-wide community-oriented service via the scalable platform. The platform provides an intake for a huge number of sensing nodes. Compute-operations following the form of data analysis, aggregation, sensors’ monitoring for the five air pollutants (SO2, CO, O3, NO2, and PM), in addition to radioactive contamination. Thus system-level performance evaluation takes place on the major compute-intensive operations. Thus, proposals are made to optimize the performance in terms of reducing the scripts execution time and the size of data and messages transmitted and stored in the system.